Governance Mechanisms and Earnings Management: Evidence from Indonesia - MUHAMMAD AGUNG PRABOWO; IRWAN TRINUGROHO; TAUFIK ARIFIN; SUTARYO SUTARYO (The Indonesian Journal of Accounting Research, 2013)
We investigate the association between ownership, board structure, audit committee size, external auditor, and accounting accruals using a dataset of Indonesian listed firms. The theoretical framework borrows from agency theory predicting that governance mechanism might discourage management from engaging in earnings manipulation. The empirical evidence supports the conditional impact of ownership, board properties, and audit committee on the level of discretionary accruals. Ownership by the ten largest shareholders is significantly related to the level of income decreasing discretionary accruals negatively. The representation of independent directors and the size of audit committee are found to have significant and negative impact on income increasing discretionary accruals. The size of the board is insignificantly related to both income increasing and decreasing accruals. The findings suggest that governance mechanisms are more likely to help mitigating agency problems in specific circumstance. However, the results of the study might suffer from measurement issues.